Tailoring Science Instruction: (Approaches for Addressing Diverse Learning Styles and Enhancing Academic Performance) - Prof. Abdulqadir Obaidallah Alhomairi (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Here’s a rephrased version of your paragraph while maintaining the original meaning: This review paper examines the use of differentiated instruction within science education, with a focus on strategies that accommodate various learning styles and enhance academic performance. It begins by exploring the theoretical foundations of differentiated instruction, addressing its definition and its connections to key learning theories. The discussion then moves into the current landscape of science education and the necessity of meeting diverse student needs. A detailed analysis of differentiated instruction strategies in science follows, covering curriculum modifications, content, process, and product differentiation, alongside the use of technology and collaborative learning. Additionally, the paper features case studies and empirical data showcasing the effectiveness of differentiated instruction, offering a comparison of success stories from different educational contexts. Challenges in implementing these strategies are also identified, along with solutions to overcome these obstacles, while emphasizing the vital role of policy and administrative support. The paper concludes by pointing to future research opportunities and reiterating the importance of differentiated instruction in creating inclusive and engaging science classrooms where all students can excel.